Heart rate variability characterization in daily physical activities using wavelet analysis and multilayer fuzzy activity clustering - Hsiao-Lung Chan; Shih-Chin Fang; Yu-Lin Ko; Ming-An Lin; Hui-Hsun Huang; Lin, C.-H. (IEEE transactions on biomedical engineering, 2006)
A portable data recorder was developed to parallel measure the electrocardiogram and body accelerations. A multilayer fuzzy clustering algorithm was proposed to classify the physical activity based on body accelerations. Discrete wavelet transform was incorporated to retrieve time-varying characteristics of heart rate variability under different physical activities. Nine healthy subjects were included to investigate activity-related heart rate variability during 24 h. The results showed that the heartbeat fluctuations in high frequencies were the greatest during lying and the smallest during standing. Moreover, very-low-frequency heartbeat fluctuations during low activity level (lying) were greater than during high activity level (nonlying).